Frequency Volatility Connectedness and Portfolio Hedging of U.S. Energy Commodities - Evžen Kočenda; Michala Moravcová (Center for Economic Studies and ifo Institute (CESifo), 2024)
We analyze (frequency) connectedness and portfolio hedging among U.S. energy commodities from 1997 to 2023. We show that the total connectedness increased over time, likely due to the increasing financialization of energy commodities. It fluctuates with respect to (i) different investment horizons and (ii) different periods of distress. The early stage of the Russia-Ukraine war is associated with the highest systemic risk, followed by the Covid-19 pandemic and global financial crisis (GFC). In the frequency domain, the results imply that investors perceive the greatest risk at longer investment horizons, particularly during the three major distress periods. We also show that despite it is difficult and more costly to diversify an energy portfolio during distress periods, adding natural gas seems to bring non-marginal diversification benefits.
Keywords: C58; F65; G15; Q34; Q41; 330; connectedness; volatility spillovers; frequency decomposition; portfolio weights and hedge ratios; energy commodities; distress